Use of the six core surgical indicators from the Lancet Commission on Global Surgery in Colombia: a situational analysis - Hanna, Joseph S; Herrera-Almario, Gabriel E; Pinilla-Roncancio, Monica; Tulloch, David; Valencia, Sergio A; Sabatino, Marlena E; Hamilton, Charles; Rehman, Shahyan U; Mendoza, Ardi Knobel; Gómez Bernal, Liliana Carolina; Salas, María Fernanda Moreno; Navarro, María Alejandra Peña; et al. (The Lancet global health, 2020)
Surgical, anaesthetic, and obstetric (SAO) health-care system strengthening is needed to address the emergency and essential surgical care that approximately 5 billion individuals lack globally. To our knowledge, a complete, non-modelled national situational analysis based on the Lancet Commission on Global Surgery surgical indicators has not been done. We aimed to undertake a complete situation analysis of SAO system preparedness, service delivery, and financial risk protection using the core surgical indicators proposed by the Commission in Colombia, an upper-middle-income country. Data to inform the six core surgical system indicators were abstracted from the Colombian national health information system and the most recent national health survey done in 2007. Geographical access to a Bellwether hospital (defined as a hospital capable of providing essential and emergency surgery) within 2 h was assessed by determining 2 h drive time boundaries around Bellwether facilities and the population within and outside these boundaries. Physical 2 h access to a Bellwether was determined by the presence of a motor vehicle suitable for individual transportation. The Department Administrativo Nacional de Estadística population projection for 2016 and 2018 was used to calculate the SAO provider density. Total operative volume was calculated for 2016 and expressed nationally per 100 000 population. The total number of postoperative deaths that occurred within 30 days of a procedure was divided by the total operative volume to calculate the all-cause, non-risk-adjusted postoperative mortality. The proportion of the population subject to impoverishing costs was calculated by subtracting the baseline number of impoverished individuals from those who fell below the poverty line once out-of-pocket payments were accounted for. Individuals who incurred out-of-pocket payments that were more than 10% of their annual household income were considered to have experienced catastrophic expenditure. Using GIS mapping, SAO system preparedness, service delivery, and cost protection were also contextualised by socioeconomic status. In 2016, at least 7·1 million people (15·1% of the population) in Colombia did not have geographical access to SAO services within a 2 h driving distance. SAO provider density falls short of the Commission's minimum target of 20 providers per 100 000 population, at an estimated density of 13·7 essential SAO health-care providers per 100 000 population in 2018. Lower socioeconomic status of a municipality, as indicated by proportion of people enrolled in the subsidised insurance regime, was associated with a smaller proportion of the population in the municipality being within 2 h of a Bellwether facility, and the most socioeconomically disadvantaged municipalities often had no SAO providers. Furthermore, Colombian providers appear to be working at or beyond capacity, doing 2690–3090 procedures per 100 000 population annually, but they have maintained a relatively low median postoperative mortality of 0·74% (IQR 0·48–0·84). Finally, out-of-pocket expenses for indirect health-care costs were a key barrier to accessing surgical care, prompting 3·1 million (6·4% of the population) individuals to become impoverished and 9·5 million (19·4% of the population) individuals to incur catastrophic expenditures in 2007. We did a non-modelled, indicator-based situation analysis of the Colombian SAO system, finding that it has not yet met, but is working towards achieving, the targets set by the Lancet Commission on Global Surgery. The observed interdependence of these indicators and correlation with socioeconomic status are consistent with well recognised factors and outcomes of social, health, and health-care inequity. The internal consistency observed in Colombia's situation analysis validates the use of the indicators and has now informed development of an early national SAO plan in Colombia, to set a data-informed stage for implementation and evaluation of timely, safe, and affordable SAO health care, within the National Public Health Decennial Plan, which is due in 2022. Zoll Medical.